FORMULASI STRATEGI BISNIS PT INDONESIA ASAHAN ALUMINIUM SETELAH PENGAMBILALIHAN OLEH PEMERINTAH - Dedi Arianto; Darwin Sitompul; Suwito Suwito (Universitas Islam Negeri Sumatera Utara, 2015)
The aim of this study is to identify the internal and external factors in the company after being taken over by the Government of Indonesia from Japanese investors and to formulate appropriate strategies to improve the performance of the company after the takeover by Indonesian government to be supporting the national aluminum industry that can fulfill the needs of the domestic aluminum and simultaneously increase profitability. This type of research is action research, with a population of 78 (seventy eight), which consists of five Directors, 21, General Managers, 49 Managers and 3 consultants in the aluminum industry. Data were analyzed with IFE and EFE matrix, then analysed by SWOT analysis and IE Matrix which produces Grow and Build strategy with the strategies used are either integrative strategy of backward integration, forward integration, as well as horizontal integration and diversification.